Periventricular lesions and MS diagnostic criteria in young adults with typical clinically isolated syndromes. (June 2017) - Brownlee, Wallace J; Miszkiel, Katherine A; Altmann, Daniel R; Ciccarelli, Olga; Miller, David H
In patients who present with a clinically isolated syndrome (CIS), whose features are suggestive of multiple sclerosis (MS), fulfilling McDonald 2010 magnetic resonance imaging (MRI) criteria for dissemination in space (DIS) and dissemination in time (DIT) enables a diagnosis of MS. While ⩾1 periventricular lesion is included in the 2010 DIS criteria, earlier McDonald criteria required ⩾3 periventricular lesions to confirm DIS and recent Magnetic Resonance Imaging in Multiple Sclerosis (MAGNIMS)-recommended DIS criteria also require ⩾3 lesions. We investigated the effect of varying the required number of periventricular lesions and found that the best combination of specificity and sensitivity for clinically definite MS was seen for ⩾1 periventricular lesion using both the McDonald 2010 and MAGNIMS 2016 criteria.